Preface: 2024 IEEE 6th International Conference on Architecture, Construction, Environment, and Hydraulics - Teen-Hang Meen; Hsi-Hsien Yang; Cheng-Fu Yang (Engineering Proceedings)
This volume presents the proceedings of the 6th International Conference on Architecture, Construction, Environment, and Hydraulics 2024 (ICACEH 2024) [...]